2014
DOI: 10.1002/2014ja019908
|View full text |Cite
|
Sign up to set email alerts
|

On the fine structure of dipolarization fronts

Abstract: Measurements from the closely spaced Cluster spacecraft are used to study the structure of the magnetic and electric fields within the magnetic ramp of dipolarization fronts (DF) observed close to the neutral sheet and the midnight meridian (YGSM<3RE). The spacecraft separation was small enough (<300 km) to treat the magnetic ramp of the DF front as a planar structure as indicated from variance analysis. The finite value of the magnetic field along the minimum variance direction for the events studied indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 38 publications
4
30
2
Order By: Relevance
“…The spatial scale of B Z pulses, L pulse , is typically of the order of a few ρ T , while the L F is less than ρ T for all analyzed pulses. This is in agreement with previous results reported for the DFs (e.g., Angelopoulos et al, 2013;Balikhin et al, 2014).…”
Section: The Dynamics and Acceleration Of Suprathermal Protons Duringsupporting
confidence: 94%
See 1 more Smart Citation
“…The spatial scale of B Z pulses, L pulse , is typically of the order of a few ρ T , while the L F is less than ρ T for all analyzed pulses. This is in agreement with previous results reported for the DFs (e.g., Angelopoulos et al, 2013;Balikhin et al, 2014).…”
Section: The Dynamics and Acceleration Of Suprathermal Protons Duringsupporting
confidence: 94%
“…They have shown the presence of intense localized and approximately fieldaligned electric currents near the leading and trailing edges of the B Z pulse. These currents can be a part of a multiscale electric current system usually associated with DFs (e.g., Fu et al, 2012;Liu et al, 2013;Balikhin et al, 2014).…”
Section: Data Descriptionmentioning
confidence: 99%
“…We find that J m is positive inside the dip region but mainly negative at the front, suggesting that dawnward current exists inside the dip region, while duskward current exists at the front (Figure 3b), consistent with previous observations (e.g., Fu et al, 2012a;Yao et al, 2013). Such difference may stem from the fact that at electron scale, DF may be more like a nonlinear structure (e.g., Balikhin et al, 2014), as seen from the conspicuous fluctuation of currents. Note that J n has a finite value with a maximum approaching 20 nA/m 2 at the front (Figure 3c), indicating that plasma can flow across the DF at electron scale.…”
Section: 1029/2018gl077928supporting
confidence: 90%
“…Interestingly, we see that J m also shows a localized positive value (in the dusk-dawn direction) in the low-density side of the DF. J l also shows a finite value at the front, with a peak approaching 13 nA/m 2 and a valley near À11 nA/m 2 (Figure 2d), indicating field-aligned/parallel currents that are expected to be associated with the DF (e.g., Balikhin et al, 2014;Liu et al, 2018;Sun et al, 2013;Yao et al, 2016). This is different from previous studies that suggested that DF may be a tangential discontinuity at subproton scale (e.g., Fu et al, 2012a;Khotyaintsev et al, 2011).…”
Section: 1029/2018gl077928contrasting
confidence: 69%
See 1 more Smart Citation